Rancang Bangun Automatic Electric Oil Heater Sebagai Pengganti Thermal Oil Boiler Berbasis IoT Pada Kapal Bulk Carrier - Fadli Sukma Pamedar; Sonhaji Sonhaji; Antony Damanik (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
From this study, the automatic electric oil heater can be used to adjust the temperature value and the automatic electric heater will be able to turn off automatically according to the setpoint temperature value determined through a smartphone device or IoT program. Monitoring can also be done with the app, as well as being able to view temperature values directly through the LCD. This tool is in the form of an electric heater that will be used to heat ship fuel automatically and is more practical and efficient. It is also easier to maintain than a boiler on a ship. The design of this tool is based on accurate calculation of temperature values, with which the process of heating up fuel becomes faster. From the results of this study, a heat sensor that can read the temperature value and the buzzer will sound and the device will automatically turn off if the temperature has reached a specified setpoint. This research was carried out when the ship was about to make a departure to find out the temperature in the heating of the fuel on the ship. Testing Design of an automatic electric oil heater as a replacement for IoT-based thermal oil boiler on this bulk carrier ship, it can be known the disadvantages and advantages of this tool, testing can be done by putting oil into the electric heater, then in a short time the oil will heat up quickly, and the tool will be able to turn off automatically and the buzzer will immediately turn on when the heat has reached the specified temperature. In the temperature setting, it can be set in a smartphone or an app that can adjust the temperature and turn off the appliance from a considerable distance. However, the application must use the internet network and cannot be accessed locally, the use of IoT requires devices and smartphones to be connected to the internet.